PERAN KONSTITUSI DALAM PEMBENTUKAN NEGARA YANG DEMOKRATIS - Gokma Toni Parlindungan S; Miasiratni Miasiratni (LPPM STIH Putri Maharaja, 2026)
The constitution is the main foundation in the formation of a democratic country. As a written basic law, the constitution functions to regulate the mechanism of power, guarantee human rights, and provide limitations on government actions so as not to exceed its authority. This study aims to analyze in depth how the constitution plays a role in forming and maintaining a democratic system of government by discussing the role of the constitution in creating a democratic system of government. This study uses a normative legal research method and uses a comparative approach. The data sources are secondary data and primary data. The analysis method uses descriptive-analytical. The results of this study are that the Constitution plays a role in forming and maintaining a democratic system of government. Thus, the role of the constitution is very significant in creating justice, freedom, and welfare in a democratic state life. This study contributes to the development of constitutional law studies, especially in understanding how constitutional mechanisms can be adjusted to the social, political, and cultural dynamics of a country without ignoring the principles of democracy. The practical implication is the importance of adaptive constitutional reform to maintain the relevance of the system of government in facing global challenges.